CORPORATE GOVERNANCE DAN NILAI PERSUHAAN: PERAN MODERASI KONSENTRASI INDUSTRI - Poh Linawati; Perminas Pangeran (Jurnal Riset Akuntansi dan Keuangan, 2017)
The purpose of this study is to examine the moderating role of industry concentration betweencorporate governance (Board of Commissioners Independent, Managerial Ownership, andInstitusional Ownership) and firm value. Industry concentration classification is calculated by theHerfindahl-Hirschman Index (HHI). In terms of chow test can be concluded that the regressionequation between sub-groups of concentrated industries and less concentrated industries differsignificantly and it shows that the industry concentration is moderating variable.Keywords: Industrial Concentration, Board Of Commissioners Independent, Managerial Ownership,Institusional Ownership, Firm Value.